2015
DOI: 10.1177/1049909115570707
|View full text |Cite
|
Sign up to set email alerts
|

Survival Prediction in Ambulatory Patients With Stage III/IV Non-Small Cell Lung Cancer Using the Palliative Performance Scale, ECOG, and Lung Cancer Symptom Scale

Abstract: The LCSS predicted prognosis best in this study. The PPS did not accurately predict prognosis in our patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…Treatments for late stage are largely palliative and platinum-based chemotherapy regimens have reached a benefit plateau [3]. Regrettably, patients diagnosed at an advanced stage have a life expectancy of <1 year [4].…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Treatments for late stage are largely palliative and platinum-based chemotherapy regimens have reached a benefit plateau [3]. Regrettably, patients diagnosed at an advanced stage have a life expectancy of <1 year [4].…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…For example, Maltoni et al 20 reported three categories (PPS 10-20%, PPS 30-50%, PPS ‡60%). Of the 13 studies, the 6 remaining 2,5,12,13,23,24 reported the initial PPS scores as discrete variables, which had different ranges of PPS scores (e.g., PPS 10-70%, PPS 40-90%). Of the six studies, two studies 2,5 reported PPS ranging from 10% to 70%, while the four remaining studies reported various ranges.…”
Section: Pps Scores At Baselinementioning
confidence: 99%
“…Of the six studies, two studies 2,5 reported PPS ranging from 10% to 70%, while the four remaining studies reported various ranges. For example, O'Mahony et al 23 reported PPS scores ranging from 40% to 90%, while Lau et al 11 reported PPS scores ranging from 10% to 80%.…”
Section: Pps Scores At Baselinementioning
confidence: 99%
“…Among them, the Lung Cancer Symptom Scale consists of a lung cancer-specific measure of QoL. This scale is used particularly in clinical trials and assesses six common symptoms associated with lung cancer, such as loss of appetite, fatigue, cough, dyspnea, hemoptysis, and pain 55. This evaluation involves the use of the visual analog scale.…”
Section: Impact Of Patient-focused Perspectives Such As Qolmentioning
confidence: 99%